Aspects of EFL University Learners’ Lexical and Phraseological Proficiency as Predictors of Writing Quality - Ait Hammou, Brahim; Larouz, Mohammed; Fagroud, Mustapha; Akki, Fouad (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2023)
This study aims to examine the relationship between the productive knowledge of some lexical and phraseological indices and the quality of English as a Foreign Language (EFL) learners’ writing. A sample of 120 expository essays, written by semesters 1 and 5 university students in a less proficient EFL context, are rated by human evaluators and automatically examined for the target indices. The results show that, unlike the index of lexical diversity, both indices of content word frequency and range could significantly discriminate between different proficiency levels. For the phraseological indices, both the proportions of rare and frequent bigrams yielded between-group differences, with higher proficiency students performing significantly better in both categories. Using a regression analysis, the results show that the use of rare and contextually restricted content words and the production of larger proportions of rare and frequent bigrams could be considered indicators of better writing proficiency. The study suggests implications for the teaching of EFL.